Pemanfaatan Limbah Kolam Lele dan Bacillus sp untuk meningkatkan pertumbuhan dan hasil Padi (Oryza sativa) - Tri Rahayuningsih (Universitas Merdeka Madiun, 2020)
Abstractâ€” Catfish pond waste has a high content of organic matter and nutrients (nitrogen) which can be used as a source of nutrition for rice plants, but on the other hand it also contains ammonia which can interfere with rice growth. Therefore, research is needed to reduce the negative effects of using catfish pond waste. in rice cultivation, by utilizing Bacillus sp. The purpose of this research is to obtain information about how to use catfish pond waste for rice cultivation, by utilizing the Bacillus sp. Bacteria. Bacillus sp is thought to increase nutrient availability for rice. The method to be carried out in this study used a randomized block design with treatment A0 (control), A1 (Bacillus sp), A2 (catfish waste), A3 (catfish waste + Bacillus sp), A4 (Urea fertilizer). The results of this study found that pond waste and Bacillus sp. Affected the growth and yield of rice. The highest results were obtained in the combination treatment of pond waste with Bacillus sp. Â Keywordsâ€”: Bacillus sp; catfish pond waste; organic rice.